Determination of Micro-Iodate in Iodized Salt by High Performance Liquid Chromatography - Chen, Meilan; Ye, Mingli; Yang, Xinlei; Fawzi, El-Sepaia (Asian Journal of Chemistry, 2014)
A novel method was developed to determine micro-iodate in iodized salt by high performance liquid chromatography via hydrazine hydrate reduction. Iodate was first reduced to iodide using 0.085 % hydrazine hydrate solution followed by HPLC analysis. The sample pretreatment process was simple without any significant interference from the large amount of chloride in the matrix sample during the final analysis. Linearity was validated in the range of 1 to 1000 μmol/L with high correlation coefficient (R2 = 0.9995) and the limit of detection (LOD) was 0.214 mg/kg (KIO3 content, S/N = 3). The relative standard deviation was less than 2 % (n = 5) and the spiked recoveries of four real samples were between 98.1 and 100.8 %. The proposed method was applicable for effective routine analysis of micro-iodate in iodized salt.